2020
DOI: 10.18632/aging.103654
|View full text |Cite
|
Sign up to set email alerts
|

Lack of retinoid acid receptor-related orphan receptor alpha accelerates and melatonin supplementation prevents testicular aging

Abstract: The role of retinoid acid receptor-related orphan receptor alpha (RORα) on male reproductive functions during aging is unclear. Here, we analyze the morphological changes in the testis of both young and aged RORα-deficient mice, with and without melatonin supplementation. Young mutants showed vacuolation, degeneration and pyknosis of spermatogenic epithelium and Sertoli cells. Aged mutants showed atrophy of the seminiferous tubules and absence of mitotic spermatogenic cells. Absence of sperms in many tubules, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 86 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…In these animals, other structural changes in the gland are seen, such as problems in the maturation of sperm and hypertrophy of Sertoli cells. In addition, Leydig cells also increase their presence in the testes with senescence (Sayed et al, 2020), taken together these data indicate that the telocytes in the testis may be sensitive to other molecular pathways in addition to the estrogenic and androgenic ones. With regard to other possible functions of the telocytes in the testes, these cells may participate in the transport of multilamellar bodies.…”
Section: Male Reproductive Systemmentioning
confidence: 91%
“…In these animals, other structural changes in the gland are seen, such as problems in the maturation of sperm and hypertrophy of Sertoli cells. In addition, Leydig cells also increase their presence in the testes with senescence (Sayed et al, 2020), taken together these data indicate that the telocytes in the testis may be sensitive to other molecular pathways in addition to the estrogenic and androgenic ones. With regard to other possible functions of the telocytes in the testes, these cells may participate in the transport of multilamellar bodies.…”
Section: Male Reproductive Systemmentioning
confidence: 91%
“…ROR α plays a complex role in regulating apoptosis in different cell types. Loss of ROR α results in progressive, diverse testicular damage and leads to apoptosis, suggesting that ROR α knockout promotes apoptosis in the testicle [ 35 ]. However, other studies revealed the proapoptosis effect of ROR α in different cell types [ 36 , 37 ], suggesting the complexity of ROR α in regulating cell senescence and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exogenous adiponectin treatment has been reported to significantly improve the testicular size, cell proliferation, insulin receptor expression, glucose uptake, antioxidant enzyme activity, and testosterone synthesis in aged mice ( 148 ). Melatonin supplementation could also rescue testicular aging caused by the loss of retinoic acid receptor-related orphan receptor alpha ( 53 ).…”
Section: Rescue and Prevention Of Reproductive Agingmentioning
confidence: 99%